A Influência do IDORT na Reconfiguração do Bloco no Poder durante o Estado Varguista entre 1931 e 1937 - Souza, Célia Aparecida de (2006)
This paperwork has the objective of examining some aspects related to IDORT - Institute of Work Rational Organisation created in 1931, with the aim, in the beginning, of rationalise the work in private companies. We can see, however, that this Institute rationalised the services of Public Administration of the State Government with the help of one of their most expressive members, Armando de Salles Oliveira, its honour president. On the same occasion, we saw that the IDORT has become a well known Institute in many Brazilian states due to the quality of its services and the intense publicity of its magazines, which led a increase in the quantity of partners interested in hire their services. Its performance, however, it was not localised just in the participation of the political society where we verify the significant performance of the IDORT people in the Constituent of 1934, in the Ministry of Exterior Relations, in the Technical Counsellors and also in the discussions that ended up creating the DASP- Administration Department of Public Services. Although there are many researches about the period due to its importance to the understanding of the Brazilian State reorganisation, in the after 1930, our research had the objective of contributing to another way of seeing the construction of a hegemony of a burgess industrial class fraction, represented by the IDORT.